User's view of the quality of Croatian topographic map at the scale 1:25 000 - Branko Puceković; Miljenko Lapaine (Geodetski Glasnik, 2016)
The subject of this research was the quality of the Croatian Topographic Map at the scale of 1:25 000 (TM25). The needed information was collected by using a questionaire. Emphasis was put on aesthetics and logical consistency. The total of 42% out of 165 users participated in the questionnaire. According to the survey, quality can be improved by these quality elements: content completeness, geometrical accuracy, geographic fidelity, contemporaneity and the aesthetic appearance. Even though aesthetics is not a priority for some, users give concrete suggestions with the objective to improve the aesthetics of TM25. Content completeness is the most important element to respondents in their work, while the aesthetics is the least important. One of the results of the research is that the Croatian TM25 is suitable for use by 99% of users.